ANALYZING TEACHING SPEAKING METHODS IN DIGITAL ERA - Isnaini, Rahma Amini; Fauzia, Fauzia (Premise: Journal of English Education and Applied Linguistics, 2024)
English is an international language used by all elements of world society and creates intense competition for every individual in the world in all aspects. To realize appropriate learning objectives, teaching speaking in English is no exception. The author aims to discover various teaching methods for students in the digital era and the problems encountered when teaching speaking in this digital era. The method used must also be appropriate for the student. This research uses a qualitative literature study design method. The data analysis used in this research reviews some literature related to a problem in this study published in the last five years (2019-2023). The findings from this research are audio-lingual, application of audio-visual, digital storytelling, debate, and using games that are relevant to be used in this digital era so that they are relevant. Then, the problems in teaching speaking are curriculum, lack of preparation in learning, and student anxiety. Every teacher must be able to recognize their students' level of ability, especially in speaking. So, the method chosen can help students to improve their speaking skills.